Preventing Sports-Related Dental Trauma: A Critical Review of Mouthguard Effectiveness, Compliance, and Clinical - Markiv, Mariana; Świercz, Jędrzej; Arciszewski , Kamil; Orda , Karolina; Hariasz , Natalia; Walczak , Dominika; Szumiło, Jakub; Kasperska , Klaudia; Słowik , Michał; Stenzel , Paweł (Journal of Education, Health and Sport, 2026)
Background: Sports-related dental trauma remains a common problem in both recreational and professional athletics, often resulting in long-term functional, esthetic, and psychological consequences. Mouthguards are widely recommended as a preventive strategy; however, differences persist between laboratory evidence and real-world clinical effectiveness. Objective: This review aimed to evaluate the effectiveness of mouthguards in preventing sports-related dental injuries, with emphasis on mouthguard types, biomechanical performance, clinical outcomes, and compliance-related factors. Methods: A structured narrative review was conducted using PubMed and Google Scholar databases. Studies published between 2015 and 2026 related to sports dentistry, dental trauma, and mouthguard effectiveness were screened. Seventeen studies, including systematic reviews, epidemiological investigations, laboratory studies, and clinical research, were included. Results: Evidence suggests that mouthguards reduce the incidence and severity of sports-related orofacial injuries. Custom-made mouthguards demonstrate superior fit, force distribution, and shock absorption compared with stock and boil-and-bite devices. However, clinical effectiveness is strongly influenced by compliance, comfort, accessibility, and enforcement of protective regulations. Evidence regarding concussion prevention remains inconsistent. Conclusions: Mouthguards are an effective preventive strategy against sports-related dental trauma, although their real-world benefit depends largely on consistent use. Future studies should focus on standardized injury definitions, prospective designs, and behavioral factors influencing adherence. Educational interventions and policy implementation may further improve preventive outcomes.